Effective Reading Instruction in ESP: Practical Approaches to Improving Vocational Students Content-Area Reading Comprehension - TAMRIN, Tamrin (Research and Innovation in Applied Linguistics, 2023)
Effective reading instruction in Vocational Higher Education (henceforth VHE) has been criticized as ineffective, as demonstrated by poor reading test results, indicating a deficient students’ reading performance. This article examines and gains insight into the reasons why things occur as they do by discussing the following four topics: (1) describing the context in which reading instruction occurs and why this instructional effort does not work as expected; (2) describing the nature of content area reading; (3) unpacking things that could potentially encourage students’ interests and increase their reading involvement, thereby making their reading more effective; and (4) proposing a set of pedagogical principles that could potentially improve the students optimal reading and comprehension